Electrode behaviour of nickel in HCl-dimethylsulphoxide solutions : I. The cathodic evolution of hydrogen - Delgado, A. (1973)
The electrochemical reduction of the solvated hydrogen ion dissolved in DMSO as HCl was investigated from 25 to 45°C, at different concentrations and ionic strength. Stationary and non-stationary techniques were employed to obtained the kinetic parameters. The results were interpreted with a reaction scheme involving an initial electron transfer as rds, probably followed by an electrochemical desorption step.